Promosi Rumah Belajar Jambi (RUMBAI) Di Kelurahan Kenali Asam Atas Kecamatan Kota Baru Kota Jambi - Amalia, Rezki; Syamsuddin, Syamsuddin; H, Siti Asiah Wahyuni (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Introduction. The study aims to identify the promotion by Rumah Belajar Jambi (RUMBAI) in in Kenali Asam Atas, Kotabaru, Jambi City. To find out the primary obstacles encountered by Rumah Belajar Jambi (RUMBAI) in Kenali Asam Atas, Kotabaru, Jambi City. Additionally, it seeks to outline the measures that will be taken to address these obstacles by Rumah Belajar Jambi (RUMBAI) in Kenali Asam Atas, Kotabaru, Jambi City. Data Collection Methods. The research is conducted using a descriptive qualitative approach and involves data collection through interviews, observation, and documentation. Data Analysis. The data analysis process includes data reduction, data presentation, and conclusion. Results and Discussion. the promotional activities of Rumah Belajar Jambi primarily involve distributing brochures to village offices and schools in the vicinity, word-of-mouth promotion, and utilizing Instagram and YouTube for social media promotion. However, the study observes that the promotional efforts through social media are not as active and creative, lacking the use of hashtags and variety in content. Internal and external factors have been identified as influencing the promotion of Rumah Belajar Jambi. Internal obstacles include funding, human resources, book collections, and time, while external obstacles include low public awareness, lack of updated information on social media, and insufficient community engagement. Efforts to address these factors include participating in literacy activities, recruiting new volunteers to enhance human resources at Jambi Learning House, and conducting promotional activities to increase visitor engagement. Conclusion. The promotions carried out by Rumah Belajar Jambi are less active and creative in carrying out promotions via social media. Such as the use of hashtags and a lack of variety of content in posts on social media. Keywords: Promotion, Library Promotion, Community Reading Park.